Thermoelectric power sources using low-grade heat: Part 1 - Anatychuk, L.I.; Prybyla, A.V.; Korop, M.M.; Kiziuk, Yu.I.; Konstantynovych, I.A. (Journal of Thermoelectricity, 2024)
This work is the first part of a series of studies on thermoelectric power sources using low-grade heat. The results of computer design of a thermoelectric generator with heat exchange by natural convection using waste heat from industrial installations are presented. The generator design was developed and a series of its experimental studies were carried out on a test bench.